Quality of pineapple fruit and evaluation of the intercropping of pineapple, cassava and cowpea beans (Bioagro, 2024)
The objective of this study was to evaluate the fruit quality of pineapple in consortium with cowpea and cassava. The experiment was conducted in the state of Roraima, Brazil, with the individual cultivation of pineapple (cv. Pérola) and in consortium with cowpea beans and cassava at different cassava spacings (0.40; 0.60; 0.80; 1.00; 1.20 m), with 14 treatments. The experimental design was a completely randomized block with three replications. The crops were planted simultaneously. The pineapple, as the main crop, was harvested at 17 months, and the following characteristics were evaluated: average fruit diameter, fruit length without crown, crown length, soluble solids content, fruit firmness without peel, and average commercial fruit weight (yield). For the other crops, productivity was evaluated to determine land use efficiency. The soluble solids content in the fruits was not affected by the treatments, with a general average of 13.35° Brix. However, the physics characteristics were negatively affected at higher cassava densities, resulting in fruits with smaller diameter and length, directly impacting productivity. The productivity of cowpea was not reduced by the consortium, similar to the productivity of cassava, which was only reduced by its lower density.
Keywords: Ananas comosus; land use efficiency; Manihot esculenta; polyculture; Vigna unguiculata